(3QhVI GdWGdHjf hYeOg GdeJbjfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s ((3CMeO Hf eMeO Hf SYO GdNGRfi s)
(3ChdgG (B:s
(3jHOF HChd cJGH GdhUGjG s
(3BNQgG (B:s
(3hjfJgi Edi BNQ HGH CegGJ GdChdGO hgh BNQ GdJCdja s
(3GdfSNI HgG MhGTs
(3aJM GdYRjR Ydi cJGH GdhLjR ddQGaYi gh TQM GdhLjR dCHi GdZRGdis
(3fSNI QGHYI s
(3hbO CJe GdeDda JCdjag SfI (B669 (3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdTGaYjs